Electrolyte solution, electrochemical device, and electronic apparatus
By using halogenated quinoline compounds as electrolyte additives in lithium-ion batteries and controlling their relationship with the positive electrode active material layer, the problem of easy breakage of organic matter-rich CEI protective film during lithium ion deintercalation is solved, and the high energy density, room temperature and high temperature performance of the battery is improved.
Patent Information
- Application Number
- CN202411919072.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-21
AI Technical Summary
In existing lithium-ion batteries, the organic-rich CEI protective film is prone to break during the lithium ion deintercalation process, resulting in side reactions and battery capacity attenuation.
Halogenated quinoline compounds are used as electrolyte additives, and the relationship with the positive electrode active material layer is regulated to form a stable protective film, satisfying the conditions of 0.03≤Ya/(L*M*N)≤2.8.
On the premise of ensuring the energy density of the battery, the battery's room temperature and high temperature performance will be improved, the destruction of the positive electrode active material will be reduced, the transition metal dissolution will be reduced, and the wetting and fluidity of the electrolyte will be improved.
Smart Images

Figure BDA0005209598140000021 
Figure BDA0005209598140000022 
Figure BDA0005209598140000031
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to electrolytes, electrochemical devices and electronic devices. Background Art
[0002] The surface of the cathode material in lithium-ion batteries is covered with a CEI protective film, which can suppress or reversibly restore the cracks caused by volume changes in the cathode, significantly improving the cycle life of the cathode. However, how to form a stable CEI to meet the needs of higher energy density is a research problem in the electrolyte field.
[0003] In the related art, functional additives are used to form an organic-rich CEI protective film between the positive electrode and the electrolyte to improve the stability of the CEI protective film. However, the organic-rich CEI is combined with the positive electrode surface and cannot withstand the large volume change of the positive electrode, resulting in breakage during the lithium ion deintercalation process, which in turn leads to continuous side reactions between the positive electrode and the electrolyte. In addition, the organic-rich CEI is easily oxidized under high voltage, which further accelerates the attenuation of the battery capacity. Summary of the invention
[0004] In order to solve or partially solve the problems existing in the related art, the present application provides an electrolyte, an electrochemical device and an electronic device, which can form a stable protective film at the positive and negative electrodes by using halogenated quinoline compounds as electrolyte additives and regulating the relationship between the electrolyte additives and the positive electrode active material layer, thereby improving the room temperature and high temperature performance of the battery while ensuring the energy density of the battery.
[0005] In a first aspect, the present application provides an electrolyte, including an electrolyte additive, wherein the electrolyte additive includes a halogenated quinoline compound, and the electrolyte additive and the positive electrode plate satisfy the following relationship:
[0006] 0.03≤Ya / (L*M*N)≤2.8
[0007] The mass percentage of electrolyte additives in electrolyte is Ya%, the total number of positive electrode active material layers is L, and the mass of positive electrode active material layers per unit area on the positive electrode sheet is M g / cm 2 , the compaction density of the positive electrode active material layer is Ng / cm 3 .
[0008] As an optional embodiment, the electrolyte additive and the positive electrode satisfy 0.27≤Ya / (L*M*N)≤0.7.
[0009] As an optional embodiment, 0.1≤Ya≤10; and / or, 10≤L≤30; and / or, 0.025≤M≤0.160; and / or, 3.2≤N≤3.5.
[0010] As an optional embodiment, 1≤Ya≤2; and / or, 10≤L≤18; and / or, 0.025≤M≤0.06; and / or, 3.2≤N≤3.4.
[0011] As an optional embodiment, the structural formula of the halogenated quinoline compound is as follows:
[0012]
[0013] In Formula 1, R1-R5 are each independently selected from a hydrogen atom, a C1-C10 halogenated or non-halogenated alkyl group, a C1-C10 halogenated or non-halogenated unsaturated alkyl group, a C7-C20 halogenated or non-halogenated aromatic group, and a halogen atom, and R1-R5 contain at least one halogen atom.
[0014] As an optional embodiment, R1-R5 are each independently selected from a hydrogen atom, a C1-C3 halogenated or non-halogenated alkyl group, a C1-C3 halogenated or non-halogenated unsaturated alkyl group, a halogenated phenyl group, a halogenated alkylphenyl group, a halogen atom, and R1-R5 contains at least one halogen atom; preferably, the halogen atom is a fluorine atom.
[0015] As an optional embodiment, the electrolyte additive is selected from at least one of the following halogenated quinoline compounds:
[0016]
[0017]
[0018] A second aspect of the present application provides an electrochemical device, comprising a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the electrolyte is the electrolyte described above.
[0019] As an optional embodiment, the positive electrode plate includes a positive electrode current collector and a plurality of positive electrode active material layers located on at least one side of the positive electrode current collector.
[0020] A third aspect of the present application provides an electronic device, comprising the electrochemical device described above.
[0021] The technical solution provided by this application may have the following beneficial effects:
[0022] On the one hand, the nitrogen-containing heterocyclic structure contained in the halogenated quinoline compound of the present application can efficiently remove trace moisture in the electrolyte, and thus can also reduce the content of HF in the system, preventing the damage of the electrode material caused by excessive HF content; at the same time, the nitrogen-containing heterocyclic structure can participate in film formation at the positive and negative electrodes, stabilize the positive and negative electrode interfaces, effectively reduce the damage to the positive electrode active material, reduce the dissolution of transition metals, and improve the high temperature performance of the battery; and the presence of a cosolvent benzene ring and an electron-withdrawing group (-CXn, where X is a halogen atom) can reduce the surface tension of the pole piece, improve the wettability of the electrolyte, and improve the fluidity of the electrolyte during the cycle, thereby improving the long cycle performance of the battery at room temperature. On the other hand, the effect of the electrolyte additive is related to the total number of layers, surface density and compaction density of the positive electrode active material. When 0.03≤Ya / (L*M*N)≤2.8 is satisfied, the effect of the electrolyte additive and the total number of layers, surface density and compaction density of the positive electrode active material can be balanced, achieving the high energy density of the lithium-ion battery while improving the room temperature performance and high temperature performance of the battery.
[0023] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. DETAILED DESCRIPTION
[0024] The embodiments of the present application will be described in more detail below. Although the embodiments of the present application are shown, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.
[0025] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0026] It should be understood that although the terms "first", "second", "third", etc. may be used in this application to describe various information, this information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of this application, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0027] In the related art, functional additives are used to form an organic-rich CEI protective film between the positive electrode and the electrolyte to improve the stability of the CEI protective film. However, the organic-rich CEI is combined with the positive electrode surface and cannot withstand the large volume change of the positive electrode, resulting in breakage during the lithium ion deintercalation process, which in turn leads to continuous side reactions between the positive electrode and the electrolyte. In addition, the organic-rich CEI is easily oxidized under high voltage, which further accelerates the attenuation of the battery capacity.
[0028] In response to the above problems, an embodiment of the present application provides an electrolyte, which can form a stable protective film at the positive and negative electrodes by using a halogenated quinoline compound as an electrolyte additive and regulating the relationship between the electrolyte additive and the positive electrode active material layer, thereby improving the room temperature and high temperature performance of the battery while ensuring the energy density of the battery.
[0029] The embodiment of the present application provides an electrolyte, including an electrolyte additive, wherein the electrolyte additive includes a halogenated quinoline compound, and the electrolyte additive and the positive electrode plate satisfy the following relationship:
[0030] 0.03≤Ya / (L*M*N)≤2.8
[0031] The mass percentage of electrolyte additives in electrolyte is Ya%, the total number of positive electrode active material layers is L, and the mass of positive electrode active material layers per unit area on the positive electrode sheet is M g / cm 2 , the compaction density of the positive electrode active material layer is Ng / cm 3 .
[0032] In the embodiment of the present application, the positive electrode sheet includes a positive current collector and a multi-layer positive active material layer located on at least one side of the positive current collector, and the positive active material layer is formed by coating the positive active slurry on the current collector, and the positive active slurry includes a positive active material, a conductive agent and a binder. Among them, the multi-layer positive active material layer can refer to a multi-layer structure formed by coating the same positive active slurry in multiple layers, and can also refer to a multi-layer structure formed by coating different positive active slurries in layers, and the present application does not limit this.
[0033] The total number of positive electrode active material layers may refer to the total number of positive electrode active material layers prepared by slurrying the positive electrode material to obtain a positive electrode active slurry and then applying a multi-layer coating method.
[0034] The mass of the positive electrode active material layer per unit area on the positive electrode sheet may refer to the surface density of the positive electrode active material layer on one side of the positive electrode sheet.
[0035] The compaction density of the positive electrode active material layer may refer to the volume density of the positive electrode active material layer after compaction under a certain pressure.
[0036] During the charging process, the lithium ions in the positive electrode will be released and embedded in the negative electrode, causing the negative electrode to expand to a certain extent. The size of the expansion is related to the total number of layers, surface density and compaction density of the positive electrode active material. When the total number of layers, surface density and compaction density of the positive electrode active material are too large, it is not conducive to the deintercalation of lithium ions. If they are too small, it will cause the positive electrode to deintercalate lithium faster, causing a mismatch in the positive and negative electrode kinetics, thereby leading to the problem of lithium precipitation. Therefore, a better total number of layers, surface density and compaction density of the positive electrode active material can not only meet the smaller expansion of the electrode during charging, but also provide suitable ion and electron conduction channels.
[0037] Furthermore, the high temperature performance of lithium-ion batteries is not only related to the physical parameters of the positive electrode active materials (such as the total number of layers, surface density and compaction density of the positive electrode active materials), but also to the electrolyte additives. Among them, as the total number of layers, surface density and compaction density of the positive electrode active materials decrease, the normal temperature performance of the battery is better, but if the total number of layers, surface density and compaction density of the positive electrode active materials are too small, the high temperature performance of the battery will deteriorate. As the total number of layers, surface density and compaction density of the positive electrode active materials increase, the high temperature performance of the battery is better, but if the total number of layers, surface density and compaction density of the positive electrode active materials are too large, it will affect the normal temperature performance of the battery. Therefore, how to improve the normal temperature performance and high temperature performance of the battery while ensuring the high energy density of the lithium-ion battery is a problem studied by the inventors of this application.
[0038] It has been found that the halogenated quinoline compounds provided in the embodiments of the present application are used as electrolyte additives, and when the total number of layers, surface density and compacted density of the electrolyte additive and the positive electrode active material meet 0.03≤Ya / (L*M*N)≤2.8, the room temperature performance and high temperature performance of the battery can be improved while ensuring the high energy density of the lithium ion battery. This is because on the one hand, the nitrogen-containing heterocyclic structure contained in the halogenated quinoline compounds of the embodiments of the present application can efficiently remove trace moisture in the electrolyte, and thus can also reduce the content of HF in the system, and prevent the damage of the electrode material caused by excessive HF content; at the same time, the nitrogen-containing heterocyclic structure can participate in film formation at the positive and negative electrodes, stabilize the positive and negative electrode interfaces, effectively reduce the damage to the positive electrode active materials, reduce the dissolution of transition metals, and improve the high temperature performance of the battery; and the presence of a cosolvent benzene ring and an electron-withdrawing group (-CXn, where X is a halogen atom) can reduce the surface tension of the pole piece, improve the wettability of the electrolyte, and improve the fluidity of the electrolyte during the cycle, thereby improving the long cycle performance of the battery at room temperature. On the other hand, the effect of electrolyte additives is related to the total number of layers, surface density and compaction density of the positive electrode active material. When 0.03≤Ya / (L*M*N)≤2.8 is satisfied, the efficacy of the electrolyte additives and the influence of the total number of layers, surface density and compaction density of the positive electrode active material can be balanced, thereby ensuring the high energy density of the lithium-ion battery while improving the battery's room temperature performance and high temperature performance.
[0039] As an optional embodiment, the electrolyte additive and the positive electrode satisfy 0.27≤Ya / (L*M*N)≤0.7.
[0040] The inventors of the present application further discovered that when the relationship between the electrolyte additive and the positive electrode satisfies 0.27≤Ya / (L*M*N)≤0.7, the battery energy density can be maximized while further improving the room temperature performance and high temperature performance of the battery.
[0041] As an optional embodiment, 0.1≤Ya≤10.
[0042] In the embodiments of the present application, Ya can be 0.1, 0.3, 0.5, 1, 2, 5, 10 or any value within the above range, and the present application does not limit this.
[0043] If the pressure is too small, it will not improve the room temperature performance and high temperature performance of the battery. If the pressure is too large, the high temperature performance will deteriorate.
[0044] As a preferred embodiment, 1≤Ya≤2.
[0045] In the embodiment of the present application, Ya can be 1, 1.5, 2 or any value in the above range, and the present application does not limit this. When Ya is within the limited range, the room temperature and high temperature performance of the battery can be significantly improved.
[0046] As an optional embodiment, 10≤L≤30.
[0047] In the embodiments of the present application, L can be 10, 12, 18, 25, 30 or any value within the above range, and the present application does not limit this.
[0048] As an optional embodiment, 0.025≤M≤0.160.
[0049] In the embodiments of the present application, M may be 0.025, 0.035, 0.06, 0.16 or any value within the above range, and the present application does not limit this.
[0050] As an optional embodiment, 3.2≤N≤3.5.
[0051] In the embodiments of the present application, N can be 3.2, 3.3, 3.4, 3.5 or any value within the above range, and the present application does not limit this.
[0052] Generally, the smaller the total number of layers, surface density and compacted density of the positive electrode active material layer, the greater the porosity of the positive electrode active material layer, the more developed the pore structure inside it, the better the ability to retain the electrolyte, the better the contact effect between the electrolyte and the positive electrode active material layer, and the better the liquid phase conductivity of lithium ions inside the pores of the positive electrode coating. However, when the total number of layers, surface density and compacted density of the positive electrode active material are too large, it is not conducive to the deintercalation of lithium ions. If they are too small, the positive electrode will deintercalate lithium faster, causing a mismatch between the positive and negative electrode kinetics, thereby causing the problem of lithium precipitation. Therefore, the embodiment of the present application limits the total number of layers, surface density and compacted density of the positive electrode active material layer to the above range, which can balance the transmission capacity of lithium ions and electrons, so that the transmission capacity of lithium ions and electrons of the positive electrode coating is relatively excellent, which is beneficial to improving the charging capacity of the lithium ion battery; at the same time, it can ensure that the positive electrode active material has a high particle integrity, and there is a good electrical contact effect between adjacent particles, which is beneficial to improving the energy density of the lithium ion battery.
[0053] As a preferred embodiment, 10≤L≤18.
[0054] In the embodiments of the present application, L can be 10, 12, 18 or any value within the above range, and the present application does not limit this.
[0055] As a preferred embodiment, 0.025≤M≤0.06.
[0056] In the embodiments of the present application, M can be 0.025, 0.035, 0.06 or any value within the above range, and the present application does not limit this.
[0057] As a preferred embodiment, 3.2≤N≤3.4.
[0058] In the embodiments of the present application, N can be 3.2, 3.3, 3.4 or any value within the above range, and the present application does not limit this.
[0059] The embodiment of the present application defines 10≤L≤18, 0.025≤M≤0.06, and 3.2≤N≤3.4, which can improve the energy density of the lithium-ion battery while improving the room temperature and high temperature performance of the battery.
[0060] As an optional embodiment, the structural formula of the quinoline compound is as follows:
[0061]
[0062] In Formula 1, R1-R5 are each independently selected from a hydrogen atom, a C1-C10 halogenated or non-halogenated alkyl group, a C1-C10 halogenated or non-halogenated unsaturated alkyl group, a C7-C20 halogenated or non-halogenated aromatic group, and a halogen atom, and R1-R5 contain at least one halogen atom.
[0063] The halogenated quinoline compounds of the embodiments of the present application include halogenated quinoline compounds and their derivatives, which contain a co-solvent benzene ring and an electron-withdrawing group (-CXn, where X is a halogen atom) that can reduce the surface tension of the electrolyte, improve the wettability of the electrolyte, and improve the fluidity of the electrolyte during the cycle, thereby improving the long-cycle performance of the battery at room temperature.
[0064] As a preferred embodiment, R1-R5 are each independently selected from a hydrogen atom, a C1-C3 halogenated or non-halogenated alkyl group, a C1-C3 halogenated or non-halogenated unsaturated alkyl group, a halogenated phenyl group, a halogenated alkylphenyl group, and a halogen atom, and R1-R5 contains at least one halogen atom, wherein the halogen atom includes F, Cl, and Br.
[0065] More preferably, the halogen atom is a fluorine atom.
[0066] As a preferred embodiment, the electrolyte additive is selected from at least one of the following halogenated quinoline compounds:
[0067]
[0068] The compounds 1-1 to 1-12 provided in the embodiments of the present application all contain nitrogen heterocyclic structures and fluorine atoms, and the fluorine atoms have strong electronegativity, which can change the electron cloud distribution of the molecule. In addition, the fluorine atoms attract the electrons on the benzene ring, causing the polarity of the molecule to change. This special electronic structure enables the halogenated quinoline compounds to reduce the surface energy and improve the wettability when interacting with the surface of other substances.
[0069] Corresponding to the aforementioned application function realization method embodiment, the present application also provides an electrochemical device, an electronic device and corresponding embodiments.
[0070] The present application provides an electrochemical device, including a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the electrolyte includes a lithium salt, a non-aqueous organic solvent and an electrolyte additive, wherein the electrolyte additive includes a halogenated quinoline compound, and the electrolyte additive and the positive electrode sheet satisfy the following relationship:
[0071] 0.03≤Ya / (L*M*N)≤2.8
[0072] The mass percentage of electrolyte additives in electrolyte is Ya%, the total number of positive electrode active material layers is L, and the mass of positive electrode active material layers per unit area on the positive electrode sheet is M g / cm 2 , the compaction density of the positive electrode active material layer is Ng / cm 3 .
[0073] Preferably, the electrolyte additive further includes fluorocarbonate.
[0074] In the embodiment of the present application, the lithium salt is selected from at least one of an organic lithium salt or an inorganic lithium salt.
[0075] Preferably, the lithium salt is selected from at least one of compounds containing fluorine and lithium.
[0076] Preferably, the lithium salt is selected from at least one of hexafluorophosphate, hexafluoroarsenate, perchlorate, trifluorosulfonyl lithium, difluoro(trifluoromethylsulfonyl)imide lithium, tris(trifluoromethylsulfonyl)methyl lithium, and bis(trifluoromethylsulfonyl)imide lithium.
[0077] Preferably, the concentration of the lithium salt is 0.5 M to 1.5 M. If the lithium salt concentration is too low, the conductivity of the electrolyte is low, which will affect the rate and cycle performance of the entire battery system; if the lithium salt concentration is too high, the viscosity of the electrolyte is too high, which will also affect the rate of the entire battery system.
[0078] More preferably, the concentration of the lithium salt is 0.8M to 1.3M.
[0079] In the embodiment of the present application, the organic solvent is selected from at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl formate, ethyl formate, ethyl propionate, propyl propionate, methyl butyrate, and tetrahydrofuran.
[0080] As an optional embodiment, the positive electrode plate includes a positive electrode current collector and a plurality of positive electrode active material layers located on at least one side of the positive electrode current collector.
[0081] The multi-layer positive electrode active material layer can be formed by coating different types of positive electrode active slurries on the positive electrode current collector in layers, or by coating the same type of positive electrode active slurry on the positive electrode current collector in batches. This application is not limited to this, and only multiple layers of positive electrode active material layers can be formed.
[0082] In the embodiments of the present application, there is no particular restriction on the type of the positive electrode current collector, which can be any known material suitable for use as a positive electrode current collector. In one embodiment, the positive electrode current collector includes metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper. Preferably, the positive electrode current collector is a metal material.
[0083] Preferably, the positive electrode active material is one or more selected from lithium cobalt oxide LiCoO2, lithium nickel manganese cobalt ternary material, lithium iron phosphate LiFePO4, and lithium manganese oxide LiMn2O4.
[0084] Preferably, the negative electrode active material is selected from graphite and / or silicon, such as natural graphite, artificial graphite, mesophase microcarbon beads (MCMB for short), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloys can be used as negative electrode active materials.
[0085] In one embodiment, the positive electrode active material layer further includes a conductive agent, a binder and a solvent.
[0086] In one embodiment, the conductive agent includes at least one of carbon materials such as natural graphite, artificial graphite, acetylene black, needle coke, carbon nanotubes, and graphene.
[0087] In one embodiment, the binder includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose.
[0088] As an optional embodiment, the negative electrode includes a negative electrode current collector and a negative electrode active slurry layer located on the negative electrode current collector, and the negative electrode active slurry layer includes a negative electrode active material.
[0089] The embodiments of the present application have no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, it can be copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector.
[0090] In the embodiments of the present application, there is no particular limitation on the material and shape of the diaphragm, as long as the effect of the present application is not significantly impaired.
[0091] In one embodiment, the separator includes a porous sheet or non-woven fabric having excellent liquid retention. The materials of the resin or glass fiber separator include, but are not limited to, polyolefin, aromatic polyamide, polytetrafluoroethylene, polyethersulfone, and the like.
[0092] In some embodiments, the electrochemical device may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0093] In some embodiments, the outer packaging of the electrochemical device may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the electrochemical device may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0094] The present application has no particular limitation on the shape of the electrochemical device, which may be cylindrical, square, or any other shape.
[0095] An embodiment of the present application also provides an electronic device, comprising the aforementioned electrochemical device.
[0096] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0097] In order to further understand the present invention, the present application is described below in conjunction with embodiments. These embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.
[0098] 1. Preparation of batteries
[0099] (1) Preparation of electrolyte
[0100] EC / PC / EMC=2 / 1 / 7 mass ratio was mixed as an organic solvent. 2% of the additive FEC was added to the organic solvent and mixed evenly, and then LiPF6 was added to obtain a mixed solution with a LiPF6 concentration of 1.1 mol / L. Then, electrolyte additives were added to the mixed solution according to the formula in Table 1 to prepare electrolytes of various embodiments and comparative examples. Among them, FEC is fluoroethylene carbonate.
[0101] (2) Production of positive electrode:
[0102] NCM811, conductive agent CNT, and binder polyvinylidene fluoride were fully stirred and mixed in N-methylpyrrolidone solvent at a weight ratio of 97:1.5:1.5 to form a uniform positive electrode slurry. The slurry was coated on the positive electrode current collector Al foil according to the total number of positive electrode active material layers L, surface density M, and compaction density N in Table 1, dried, and cold pressed to obtain the positive electrode sheets of each embodiment and comparative example.
[0103] (3) Production of negative electrode sheet:
[0104] The negative electrode active material graphite, the conductive agent acetylene black, the binder styrene butadiene rubber, and the thickener sodium carboxymethyl cellulose are fully stirred and mixed in a proper amount of deionized water solvent at a mass ratio of 95:2:2:1 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector Cu foil, dried, and cold pressed to obtain a negative electrode sheet.
[0105] (4) Production of lithium-ion batteries:
[0106] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order, so that the separator is in the middle of the positive and negative electrodes to play an isolating role, and then wound to obtain a bare cell. The bare cell is placed in an outer packaging bag, and the electrolytes in Table 1 are respectively injected into the dried battery. After vacuum packaging, standing, formation, shaping and other processes, the preparation of the lithium-ion battery is completed.
[0107] Table 1 Recipe
[0108]
[0109]
[0110]
[0111] 2. Performance Test
[0112] (1) Battery cycle test at room temperature
[0113] Test method: Place the battery in an environment of 25±2 degrees, follow the standard charge and discharge cycle, cycle rate 1C, charging voltage 3.0-4.3V, and calculate the capacity retention rate of the battery after the cycle. The calculation formula is as follows:
[0114] The nth cycle capacity retention rate (%) = (nth cycle discharge capacity) / (first cycle discharge capacity)*100%.
[0115] (2) High temperature cycle test of batteries
[0116] Test method: Place the battery in a 45±2 degree environment, follow the standard charge and discharge cycle, cycle rate 1C, charging voltage 3.0-4.3V, and calculate the capacity retention rate of the battery after the cycle. The calculation formula is as follows:
[0117] The nth cycle capacity retention rate (%) = (nth cycle discharge capacity) / (first cycle discharge capacity)*100%.
[0118] (3) High temperature storage test of batteries:
[0119] Test method: Charge the divided battery cells to 4.3V at room temperature with a current of 0.5C, place the fully charged battery in an environment of 85 degrees for 12 hours, measure the thickness expansion rate by heat, and after returning to room temperature, discharge the battery cells to 3.0V with a current of 0.5C and record the discharge capacity.
[0120] (4) Wetting test of the electrode
[0121] Test method: Cut the rolled positive electrode into small pieces of 5cm*5cm, fix them on a flat glass sheet, absorb 0.2g of electrolyte and drop it on the surface of the electrode each time, and record the time it takes for the electrode to be completely soaked.
[0122] (5) Surface tension test of electrolyte
[0123] Clean the platinum plate and make sure there is no impurity on the surface. Then pour the electrolyte to be tested into a clean container, immerse the platinum plate in the electrolyte, wait for it to stabilize, and then read the surface tension value. Repeat the test three times and take the average value of the three times.
[0124] The battery test results are shown in Table 2.
[0125] Table 2 Test results
[0126]
[0127]
[0128]
[0129] Combining the data in Table 1 and Table 2, by comparing Examples 1 to 28, and by comparing Comparative Examples 13 to 16, it can be seen that when 0.03≤Ya / (L*M*N)≤2.8 is satisfied, the effect of the electrolyte additive and the total number of layers, surface density and compaction density of the positive electrode active material can be balanced, achieving high energy density of the lithium-ion battery while improving the room temperature performance and high temperature performance of the battery. Further comparison of Examples 4 and 5, Example 8 and Example 9, Example 12, Examples 14 to 28, and Comparative Examples 9 and 10 shows that when 0.27≤Ya / (L*M*N)≤0.7 is further satisfied, the room temperature performance and high temperature performance of the battery can be further improved while maximizing the battery energy density.
[0130] By comparing Examples 1 to 7, it can be seen that as the mass percentage Ya of the electrolyte additive in the electrolyte increases, the room temperature performance and high temperature performance of the battery are improved, the time for the electrolyte to completely infiltrate the electrode is shortened, and the surface tension of the electrode is reduced. This is because the electrolyte additive can reduce the surface tension of the electrode and improve the wettability of the electrolyte. In addition, due to the film-forming effect of the electrolyte additive, appropriately increasing its content can improve the room temperature and high temperature performance; however, as the content Ya of the electrolyte additive further increases, the room temperature performance and high temperature performance of the battery decrease, the time for the electrolyte to completely infiltrate the electrode is prolonged, and the surface tension of the electrode is increased. This is because an excessive content of the electrolyte additive will significantly increase the viscosity of the electrolyte, resulting in a prolonged infiltration time and increased electrode tension. At the same time, in terms of film formation, an excessively high content of the electrolyte additive will significantly deteriorate the positive and negative electrode impedance and deteriorate the high temperature performance. Further combined with Comparative Examples 1 to 3, it can be seen that when the mass percentage Ya of the electrolyte additive in the electrolyte is too small, the normal temperature and high temperature performance of the battery will be poor, and the time for the electrolyte to completely infiltrate the pole piece is too long; when the mass percentage Ya of the electrolyte additive in the electrolyte is too much, it will also lead to poor normal temperature and high temperature performance of the battery, and the time for the electrolyte to completely infiltrate the pole piece is too long; and when 0.1≤Ya≤10, the normal temperature and high temperature performance of the battery can be improved at the same time, and the time for the electrolyte to completely infiltrate the pole piece can be shortened. Further combined with Examples 4 and 5, it can be seen that when 1≤Ya≤2, the normal temperature and high temperature performance of the battery can be further improved, and the time for the electrolyte to completely infiltrate the pole piece can be further shortened.
[0131] By comparing Example 4, Example 8 to Example 11, it can be seen that as the total number of layers L of the positive electrode active material layer increases, the normal temperature performance of the battery decreases and the high temperature performance increases, and the time for the electrolyte to completely infiltrate the pole piece and the surface tension of the pole piece remain basically unchanged. This is because the normal temperature performance is mainly due to the increase in the total number of layers L of the positive electrode active material layer, which makes the conduction distance of electrons in the electrode longer, which deteriorates the internal resistance of the battery cell and causes the normal temperature cycle to deteriorate. Therefore, the increase in the total number of layers L of the positive electrode active material layer will increase the polarization of the battery cell. When the charge reaches the cut-off potential, the actual potential of the positive electrode will become lower due to the existence of a larger polarization, thereby improving the high temperature performance; and the pole piece infiltration time and surface tension are mainly related to the content of the electrolyte additive, the mass M of the positive electrode active material layer per unit area on the positive electrode pole piece, and the compaction density N of the positive electrode active material layer, and are not greatly related to the total number of layers L of the positive electrode active material layer. Further combined with Comparative Examples 5 and 6, it can be seen that when the total number of positive electrode active material layers L is too small, the high temperature performance of the battery will be poor, and when the total number of positive electrode active material layers L is too large, the low temperature performance of the battery will be poor, and when 10≤L≤30, the normal temperature and high temperature performance of the battery can be improved while maintaining the high energy density of the battery. Further combined with Examples 4, 8 and 9, it can be seen that when 10≤L≤18, the normal temperature and high temperature performance of the battery can be further improved while maintaining the high energy density of the battery.
[0132] By comparing Example 4, Example 12 and Example 13, it can be known that as the mass M of the positive electrode active material layer per unit area on the positive electrode plate increases, the room temperature performance of the battery decreases and the high temperature performance increases, the time for the electrolyte to completely infiltrate the plate is prolonged, and the surface tension of the plate is increased. This is because as the mass M of the positive electrode active material layer per unit area on the positive electrode plate increases, the lithium ion diffusion path becomes longer, which will lead to increased polarization, decreased kinetic performance, and decreased room temperature performance. After the polarization becomes larger, the actual potential of the positive electrode will become lower when charging is cut off, so the high temperature performance will become better; and the larger the mass M of the positive electrode active material layer per unit area on the positive electrode plate, the thicker the plate will become, and infiltration will become more difficult, so the time for the electrolyte to completely infiltrate the plate will be prolonged, and the surface tension of the plate will be greater. Further combined with Comparative Examples 7 and 8, it can be seen that when the mass M of the positive electrode active material layer per unit area on the positive electrode sheet is too small, the high temperature performance of the battery will be poor. When the mass M of the positive electrode active material layer per unit area on the positive electrode sheet is too much, the normal temperature performance of the battery will be poor. When 0.025≤M≤0.160, the normal temperature and high temperature performance of the battery can be improved while maintaining the high energy density of the battery, and the time for the electrolyte to completely infiltrate the electrode sheet can be shortened. Further combined with Example 4 and Example 12, it can be seen that when 0.025≤M≤0.06, the normal temperature and high temperature performance of the battery can be further improved while maintaining the high energy density of the battery, and the time for the electrolyte to completely infiltrate the electrode sheet can be further shortened.
[0133] By comparing Example 4 and Example 14 to Example 16, it can be known that with the increase of the compaction density N of the positive electrode active material layer, the room temperature performance of the battery decreases and the high temperature performance increases, and the time for the electrolyte to completely infiltrate the electrode and the surface tension of the electrode also increase. This is because the increase in the compaction density N of the positive electrode active material layer will reduce the porosity of the electrode, resulting in the narrowing of the diffusion channel of lithium ions. In the room temperature cycle, the diffusion rate of lithium ions slows down, resulting in a decrease in room temperature performance; while in the high temperature cycle process, with the expansion and contraction of the material itself, appropriately increasing the compaction density N of the positive electrode active material layer can make the combination of the positive electrode active material, the conductive agent, and the binder tighter, and can maintain the integrity of the electrode in the high temperature cycle, reduce the shedding of the positive electrode active material, and improve the high temperature performance; and increasing the compaction density N of the positive electrode active material layer will make the electrode tighter, so that infiltration will become more difficult, and the surface tension of the electrode will also be greater. Further combined with Comparative Examples 9 to 11, it can be seen that when the compaction density N of the positive electrode active material layer is too small, the high temperature performance of the battery will be poor, and when the compaction density N of the positive electrode active material layer is too large, the low temperature performance of the battery will be poor, and when 3.2≤N≤3.5, the normal temperature and high temperature performance of the battery can be improved while maintaining the high energy density of the battery, and the time for the electrolyte to completely infiltrate the pole piece can be shortened. Further combined with Example 4, Example 14 to Example 15, it can be seen that when 3.2≤N≤3.4, the normal temperature and high temperature performance of the battery can be further improved while maintaining the high energy density of the battery, and the time for the electrolyte to completely infiltrate the pole piece can be further shortened.
[0134] Although the present application has been described with reference to preferred embodiments, it will be appreciated by those skilled in the art that various changes may be made and equivalents may be substituted for its elements without departing from the scope of the present application. In addition, many modifications may be made to adapt specific situations or materials to the teachings of the present application without departing from the substantive scope of the present application. Therefore, the present application is not intended to be limited to the specific embodiments disclosed as the best mode of implementing the present application contemplated, but the present application will include all embodiments falling within the scope of the appended claims.
[0135] All ranges disclosed in this application are inclusive of the endpoints, and the endpoints are combinable with each other.
[0136] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. An electrolyte, characterized in that: The electrolyte additive includes a halogenated quinoline compound, and the electrolyte additive and the positive electrode plate satisfy the following relationship: 0.03≤Ya / (L*M*N)≤2.8 The mass percentage of electrolyte additives in electrolyte is Ya%, the total number of positive electrode active material layers is L, and the mass of positive electrode active material layers per unit area on the positive electrode sheet is Mg / cm 2 , the compaction density of the positive electrode active material layer is N g / cm 3 .
2. The electrolyte according to claim 1, characterized in that The electrolyte additive and the positive electrode satisfy 0.27≤Ya / (L*M*N)≤0.
7.
3. The electrolyte according to claim 1 or 2, characterized in that 0.1≤Ya≤10; and / or, 10≤L≤30; and / or, 0.025≤M≤0.160; and / or, 3.2≤N≤3.
5.
4. The electrolyte according to claim 3, characterized in that 1≤Ya≤2; and / or, 10≤L≤18; and / or, 0.025≤M≤0.06; and / or, 3.2≤N≤3.
4.
5. The electrolyte according to claim 1, characterized in that The structural formula of the halogenated quinoline compound is as follows: In Formula 1, R1-R5 are each independently selected from a hydrogen atom, a C1-C10 halogenated or non-halogenated alkyl group, a C1-C10 halogenated or non-halogenated unsaturated alkyl group, a C7-C20 halogenated or non-halogenated aromatic group, and a halogen atom, and R1-R5 contain at least one halogen atom.
6. The electrolyte according to claim 5, characterized in that R1-R5 are each independently selected from a hydrogen atom, a C1-C3 halogenated or non-halogenated alkyl group, a C1-C3 halogenated or non-halogenated unsaturated alkyl group, a halogenated phenyl group, a halogenated alkylphenyl group, and a halogen atom, and R1-R5 contains at least one halogen atom; preferably, the halogen atom is a fluorine atom.
7. The electrolyte according to claim 5 or 6, characterized in that The electrolyte additive is selected from at least one of the following halogenated quinoline compounds:
8. An electrochemical device, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the electrolyte is the electrolyte according to claims 1 to 7.
9. The electrochemical device according to claim 8, characterized in that The positive electrode sheet includes a positive electrode current collector and a plurality of positive electrode active material layers located on at least one side of the positive electrode current collector.
10. An electronic device, characterized in that: Comprising the electrochemical device as claimed in claim 8 or 9.
Citation Information
Patent Citations
Electrolyte additive and lithium ion battery containing electrolyte additive
CN102324564A
Electrolyte additive, lithium battery electrolyte, preparation method and lithium ion battery
CN115692848A
Electrolyte additive as well as preparation method and application thereof
CN116315085A
Secondary battery and electric device
CN117497827A
Functional additive for conductive paste as well as preparation method and application of functional additive
CN118290466A